Peralihan Kerukunan Pasif menuju Kerukunan Aktif dalam Interaksi Antarumat Beragama di Kota Sukabumi - Hamdan Hamdani; Theguh Saumantri; Fauzan Akbar Novianto; Ujang Suryadi; Datu Jatmiko (Journal of Religion and Social Transformation, 2026)
Indonesia is widely recognized as a country with a high level of diversity, encompassing ethnic, cultural, and religious dimensions. This diversity constitutes a national asset; however, it also presents challenges in maintaining social harmony and cohesion. This study aims to analyze the dynamics of social interaction among religious communities in Sukabumi City, particularly in the process of transitioning from passive harmony to active harmony. The research employs a descriptive qualitative approach. Data were collected over a six-month period through observation, in-depth interviews with eight informants, including religious leaders (KA, AS, HT), a local community member (R), a local government official (AT), a representative of the Indonesian Ulema Council (NS), and a representative of the Religious Harmony Forum (MR), as well as document analysis. The findings indicate that interreligious interactions in Sukabumi City have undergone a significant shift from passive harmony, characterized by the absence of conflict to active harmony, marked by interfaith cooperation and intensive dialogue. The role of the Religious Harmony Forum (FKUB) has been a key factor in promoting and sustaining social harmony. Theoretically, this study contributes to enriching the body of knowledge on active harmony within the context of pluralistic societies. Practically, it provides insights into patterns of cooperation that may serve as a model for other regions in fostering active harmony. Furthermore, the findings offer a foundation for local governments to formulate policies that mainstream diversity as a valuable asset.